Placement of a fast ion loss detector array for neutral beam injected particles in Wendelstein 7-X. (1st March 2022) - Kulla, D; Lazerson, S; Günter, S; Hirsch, M; Hartmann, D; McNeely, P; Rust, N; Wolf, R C; ,
Abstract: In light of measuring the fast ionized particle confinement in the stellarator Wendelstein 7-X, particles generated by the neutral beam injection system are simulated to determine the placement of an array of Faraday-cup fast ion loss detectors. This array is important due to the localization of the loss pattern, which changes drastically with experimental parameters. The Monte Carlo codes BEAMS3D and ASCOT5 are used for the simulations, following the particles from injection to wall collision. Different magnetic configurations and plasma pressures are investigated in this manner, and a configuration suitable for measuring the loss fraction is found. It qualitatively reproduces the global losses, is installable in locations of current carbon wall-tiles and the individual detector output appears well-suited for experimental purposes.